Maternal quality of life in the postpartum period - Kanadys, Katarzyna; Giermasińska, Angelika; Pytka, Monika Barbara; Pilewska-Kozak, Anna B. (Nursing in the 21st Century, 2022)
MATERNAL QUALITY OF LIFE IN THE POSTPARTUM PERIODIntroduction. Quality of life is a concept which can be considered from an objective and subjective perspective. The level of life quality is determined by a number of factors, both those dependent on us and those beyond our control.Aim. Reports in the literature indicate that changes in the biological, psychological, and social spheres that occur during pregnancy and the postpartum period can aff ect women’s quality of life. Therefore, a study was undertaken to evaluate the relation betweenthe quality of life of women in the postpartum period and socio-demographic variables.Material and method. The study included 350 postpartum women. The research method was a diagnostic survey carried out with the use of the Polish version of EQ-5D-5L Health Questionnaire, which is a standardized tool, and an original questionnaire was used to collect the socio-demographic data.Results. Postpartum women were mainly characterized by high and average levels of quality of life. Encouragingly, only one in ten postpartum women in the present study experienced a low level of quality of life. Perception of quality of life of postpartum women was diff erentiated by their occupational status and fi nancial situation. Women who were studying or learning and those who declared being in a worse fi nancial situation predominated in the group with a low quality of life. Other variables, such as age, level of education and marital status, did not aff ect the quality of life of postpartum women.